The EFSUMB Guidelines and Recommendations for the Clinical Practice of Contrast-Enhanced Ultrasound (CEUS) in Non-Hepatic Applications: Update 2017 (Long Version) - Sidhu, Paul S.; Cantisani, Vito; Dietrich, Christoph F.; Gilja, Odd Helge; Saftoiu, Adrian; Bartels, Eva; Bertolotto, Michele; Calliada, Fabrizio; Clevert, Dirk-André; Cosgrove, David; Deganello, Annamaria; D’Onofrio, Mirko; Drudi, Francesco Maria; Freeman, Simon; Harvey, Christopher; Jenssen, Christian; Jung, Ernst-Michael; Klauser, Andrea Sabine; Lassau, Nathalie; Meloni, Maria Franca; Leen, Edward; Nicolau, Carlos; Nolsoe, Christian; Piscaglia, Fabio; Prada, Francesco; Prosch, Helmut; Radzina, Maija; Savelli, Luca; Weskott, Hans-Peter; Wijkstra, Hessel (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
The updated version of the EFSUMB guidelines on the application of non-hepatic contrast-enhanced ultrasound (CEUS) deals with the use of microbubble ultrasound contrast outside the liver in the many established and emerging applications.
Keywords: vascular; urinary tract; neurology; musculoskeletal system; head/neck